Fibrosis in fat: From other diseases to Crohn’s disease - Xiong, Shanshan; Tan, Jinyu; Wang, Yu; He, Jinshen; Hu, Fan; Wu, Xiaomin; Liu, Zishan; Lin, Sinan; Li, Xuehua; Chen, Zhihui; Mao, Ren (Frontiers in Immunology, 2022)
Creeping fat is a specific feature of Crohn’s disease (CD) and is characterized by mesenteric fat wrapping around the intestine. It highly correlates with intestinal transmural inflammation, muscular hypertrophy, fibrosis, and stricture formation. However, the pathogenesis of creeping fat remains unclear. Molecular crosstalk exists between mesenteric fat and the intestine. Indeed, creeping fat contains different types of cells, including adipocytes and immune cells. These cell types can produce various cytokines, fatty acids, and growth factors, which affect the mesenteric fat function and modulate intestinal inflammation and immunity. Moreover, adipocyte progenitors can produce extracellular matrix to adapt to fat expansion. Previous studies have shown that fat fibrosis is an important feature of adipose tissue malfunction and exists in other diseases, including metabolic disorders, cancer, atrial fibrillation, and osteoarthritis. Furthermore, histological sections of CD showed fibrosis in the creeping fat. However, the role of fibrosis in the mesenteric fat of CD is not well understood. In this review, we summarized the possible mechanisms of fat fibrosis and its impact on other diseases. More specifically, we illustrated the role of various cells (adipocyte progenitors, macrophages, mast cells, and group 1 innate lymphoid cells) and molecules (including hypoxia-inducible factor 1-alpha, transforming growth factor-beta, platelet-derived growth factor, and peroxisome proliferator-activated receptor-gamma) in the pathogenesis of fat fibrosis in other diseases to understand the role of creeping fat fibrosis in CD pathogenesis. Future research will provide key information to decipher the role of fat fibrosis in creeping fat formation and intestinal damage, thereby helping us identify novel targets for the diagnosis and treatment of CD.